Key technology breakthrough in new energy vehicles: Configuration path evolution from innovative ecosystem perspective - Liu, Qin; Wen, Xiaonan; Peng, Huatao; Cao, Qinwei (Journal of cleaner production, 2023)
There are still key technological bottlenecks in new energy vehicle (NEV). It is necessary to achieve key technological breakthroughs through interaction of various elements in innovation ecosystem. We constructed an innovation ecosystem with subject and environment elements as antecedent variables, and data comes from the city statistical yearbook and statistical bulletin. We constructed the comprehensive index of key technology innovation performance, and data comes from Incopat global patent database. We analyzed the sample of 62 listed NEV enterprises from 2011 to 2020 by fuzzy-set qualitative comparative analysis (fsQCA) and necessary condition analysis (NCA). The results show that: (1) The key technological breakthrough in NEV requires interaction of multiple elements, and single element does not constitute a necessary condition; (2) The configuration of breakthrough path evolves dynamically, from infrastructure-government dual driven, to economy-service dual driven, then to technology-government dual driven, and last to technology-consumer dual driven; (3) The key elements’ necessary degrees measured by bottleneck level change dynamically. This study improves theoretical value of key technology bottleneck breakthrough based on innovation ecosystem, and provides practical value for enterprises and governments to improve effective coordinate relationship with multiple elements interaction in innovation ecosystem.